When work support does not work: investigating the joint moderating effect of challenge stressors and hindrance stressors on safety compliance. Issue 1 (2nd January 2023) - Chen, Long; Chen, Ming
Abstract : This study explores the within-person relationship between work support and safety compliance, as this has not been addressed by previous scholars. Drawing from the job demands–resources model, we argue for the positive impact of daily work support on daily safety compliance. We examined this hypothesis by collecting 221 daily diary data from 50 medical care personnel. The results show that the relationship between daily work support and daily safety compliance is positive and jointly moderated by challenge and hindrance stressors. Specifically, the positive relationship between daily work support and daily safety compliance is enhanced when there are high levels of challenge and hindrance stressors, and when there are high levels of challenge stressor and low levels of hindrance stressor. In addition, this positive relationship is not significant when there are low levels of challenge stressor and high levels of hindrance stressor.